Penyusunan Kriteria Rumah Tinggal Berkonsep Ergo-Ekologi dalam Upaya Peningkatan Kenyamanan Termal Penghuni - Lusi Susanti; Sri Zetli (Jurnal Optimasi Sistem Industri, 2016)
Nowadays, developers of residential houses often neglect to pay attention about the air circulation as one of the factors that affects thermal comfort zones inside the room environment. In general, people overcome the thermal discomfort using mechanical ventilation such as a fan or Air Conditioning (AC).This study measured the comfort zone of 32 row houses in the Batam city with two types of floor area (LT ≤ 36 m2 and LT > 36 m2). Other variables include Ceiling Height (Tpi), Aperture Area (Vi), Wall Materials (Bhi) and Orientation (Ori) were also considered in this measurement. The results show that thermal comfort zone was influenced by the wall material (Bh1) made from brick, aperture area (V2) > 20% of the floor area, and ceiling height (Tp2) > 3 m. While the house orientation variable can still be received by utilizing the architecture techniques to reduce direct solar radiation. This study also formulated three models of row house design with ergo-ecological concept, which are Ree = f {Lti, Bh, V, Tp2, Ori} atau Ree = f {Lt2, Bh, V, Tp1, Or2} atau Ree = f {Lt1, Bh, V, Tp1, Or1}.